Determinants of mortality and impact of therapy in patients with leptospirosis admitted for intensive care in a Sri Lankan hospital – a three year retrospective study. (17th November 2015) - Weeratunga, P. N.; Fernando, S.; Sriharan, S.; Gunawardena, M.; Wijenayake, S.
Abstract : Introduction: Leptospirosis is a disease of epidemic proportions in Sri Lanka. There is paucity of data on the determinants of mortality and impact of therapy in patients with leptospirosis admitted to critical care settings in endemic territories. Methodology: This retrospective cross-sectional study was performed in patients with serologically confirmed leptospirosis admitted to the intensive care unit of the General Hospital, Kalutara from January 2011 to April 2014. Associations between socio-epidemiological, clinical and laboratory parameters and patient mortality were examined. Results: Forty-five patients were included. The mean age was 49.11(SD = 16.95) and majority (92%) were male. Percentage mortality was 44.4%. Patient mortality was associated with age > 40 ( p  = 0.012), symptoms of uremia ( p  = 0.017), evidence of CNS involvement ( p  = 0.039), presence of oliguria ( p  = 0.002) and anuria ( p  = 0.014), presence of multi-organ dysfunction syndrome (MODS) ( p  < 0.001), CRP > 96 ( p  = 0.036), platelet count < 20, 000 ( p  = 0.045), Potassium > 5.0 ( p  = 0.05), metabolic acidosis with pH < 7.2 ( p  = 0.03), INR > 2 ( p  = 0.037) and requirement of mechanical ventilation ( p  < 0.001). Cox regression analysis revealed MODS and potassium > 5 to be independently associated with mortality. Conclusions: A high mortality rate is noted. The presence of MODS and serum potassium concentration > 5.0 was independently associated with mortality in this retrospective study of patients with confirmed leptospirosis in a critical care setting.